A Rare Case “Human Tail” Associated with Lipomeningocele and Tethered Cord - Pangestu, Teguh; Aji, Prihartomo Gatot (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2022)
The human tail is perhaps the most exciting sign of a neural tube defect in the skin. From the appendix until creating a 20 cm long tail-like lesions are reported in this literature. They may occur associated with an underlying pathology condition such as a lipoma or teratoma, but mostly, they hide the underlying spinal dissrafism. Here, we are presenting a case of a 5-year-old female who presented with an 18-cm long tail, which the tail hid till this age because of social stigma and shame. This is the most extended human tail reported of our knowledge in Indonesia. Many classifications about the human tail have been suggested in history. However, regardless of the type, the primary approach to this lesson is always the same. They investigated the possibility of spinal dissrafism with pathology that occurs concurrently and planned treatment based on the patient. In neurosurgery, our goal is to determine the pathology that co-occurred accurately, fixes defects, and correct aesthetics so that the patient can be more confident and for the follow-up on pediatric patients regarding their development.